2004
DOI: 10.1093/molehr/gah114
|View full text |Cite
|
Sign up to set email alerts
|

Multiple displacement amplification on single cell and possible PGD applications

Abstract: Multiple displacement amplification (MDA) is a technique used in the amplification of very low amounts of DNA and reported to yield large quantities of high-quality DNA. We used MDA to amplify the whole genome directly from a single cell. The most common techniques used in PGD are PCR and fluorescent in-situ hybridization (FISH). There are many limitations to these techniques including, the number of chromosomes diagnosed for FISH or the quality of DNA issued from a single cell PCR. This report shows, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 20 publications
5
76
0
Order By: Relevance
“…4B). The individual marker ADO rates ranged from 0%-33.3%, consistent with previously reported marker ADO rates from similar WGA products (16,17,(27)(28)(29)(30). Thus, the tridecaplex panel demonstrated its versatility for single-cell PGD analysis, either directly or after WGA.…”
Section: Validation On Single Cellssupporting
confidence: 86%
See 1 more Smart Citation
“…4B). The individual marker ADO rates ranged from 0%-33.3%, consistent with previously reported marker ADO rates from similar WGA products (16,17,(27)(28)(29)(30). Thus, the tridecaplex panel demonstrated its versatility for single-cell PGD analysis, either directly or after WGA.…”
Section: Validation On Single Cellssupporting
confidence: 86%
“…3 (3, 4 ). HTT alleles are classified based on the number of CAG repeats: normal (Յ26 CAGs), intermediate (27)(28)(29)(30)(31)(32)(33)(34)(35), HD-causing with reduced-penetrance (36 -39 CAGs), and HDcausing with full-penetrance (Ն40 CAGs). Clinical symptoms of HD progress gradually, usually with cognitive and psychiatric manifestations appearing first followed by movement abnormalities and, finally, death (5,6 ).…”
mentioning
confidence: 99%
“…In August 2007, we adopted the platform of WGA for PGD. Such WGA amplifies a major portion of the genome of single cells with good reproducibility, 4 and enables direct mutation detection and linkage analysis simultaneously for accurate determination of the genotype of embryos. We reported our first live birth after PGD for Huntington's disease (HD) using WGA in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Using the MDA products as a template, we performed only a single round of PCR, which decreases the time required for the PGD program. This strategy is a reliable protocol for obtaining material from a sample with a minuscule amount of DNA, such as a single cell, and several reports have demonstrated high amplification rates (88-100%) with an ADO rate of 7-31% when using MDA-amplified DNA as a template (Handyside et al, 2004;Hellani et al, 2004Hellani et al, , 2005Burlet et al, 2006;Lledo et al, 2007). In particular, Burlet et al (2006) reported successful diagnosis, pregnancy and delivery in the PGD program using MDA for FXS.…”
Section: Discussionmentioning
confidence: 99%